A Validity Reassessment of the Recovery Experience Questionnaire with Two Extended Confirmatory Factor Analyses. - Hao, Leilei; Yu, Xiaoman; Meng, Hui (International Journal of Mental Health & Addiction, 2024)
Recovery experience during off-job time is crucial for understanding individuals' health and well-being. This study aimed to further evaluate the construct validity of the Recovery Experience Questionnaire (REQ) using two extended confirmatory factor analyses (CFA). In study 1, we conducted a systematic literature review of articles using the REQ. Results of the analyses supported a two-factor second-order model whereby psychological detachment and relaxation loaded one factor (buffer-oriented strategies), and mastery and control loaded another (supply-oriented strategies). In study 2, 152 participants completed an online survey on five consecutive working days (N = 725 observations). Multi-level CFA indicated that the four-factor first-order model and the two-factor second-order model fit the data better than alternative models at both the between-person and within-person levels. The factor loadings of all items were significantly lower for the day level in comparison to the between-person level. Theoretical and practical implications and further research are discussed.